Differential Calcium Dependence of Axonal Versus Somatodendritic Dopamine Release, with Characteristics of Both in the Ventral Tegmental Area - Chen, Billy T.; Patel, Jyoti C.; Moran, Kimberly A.; Rice, Margaret E. (Frontiers in Systems Neuroscience, 2011)
Midbrain dopamine (DA) neurons in the substantia nigra pars compacta (SNc) and ventral tegmental area (VTA) exhibit somatodendritic release of DA. Previous studies indicate a difference between the Ca2+ dependence of somatodendritic DA release in the SNc and that of axonal DA release in dorsal striatum. Here, we evaluated the Ca2+ dependence of DA release in the VTA and nucleus accumbens (NAc) shell for comparison with that in the SNc and dorsal striatum. Release of DA was elicited by single-pulse stimulation in guinea-pig brain slices and monitored with subsecond resolution using carbon-fiber microelectrodes and fast-scan cyclic voltammetry. In dorsal striatum and NAc, DA release was not detectable at extracellular Ca2+ concentrations ([Ca2+]o) below 1 mM; however, a progressive increase in evoked extracellular DA concentration ([DA]o) was seen with [Ca2+]o ≥ 1.5 mM. By contrast, in SNc and VTA, robust increases in [DA]o could be elicited in 0.25 mM [Ca2+]o that were ∼60% of those seen in 1.5 mM [Ca2+]o. In SNc, a plateau in single-pulse evoked [DA]o was seen at [Ca2+]o ≥ 1.5 mM, mirroring the release plateau reported previously for pulse-train stimulation in SNc. In VTA, however, evoked [DA]o increased progressively throughout the range of [Ca2+]o tested (up to 3.0 mM). These functional data are consistent with the microanatomy of the VTA, which includes DA axon collaterals as well as DA somata and dendrites. Differences between axonal and somatodendritic release data were quantified using Hill analysis, which showed that the Ca2+ dependence of axonal DA release is low affinity with high Ca2+ cooperativity, whereas somatodendritic release is high affinity with low cooperativity. Moreover, this analysis revealed the dual nature of DA release in the VTA, with both somatodendritic and axonal contributions.